PERAN ATRIBUSI KAUSAL DALAM PENINGKATAN PRESTASI AKADEMIK - ASINA CHRISTINA ROSITO (LP2MTBM MAKARIOZ, 2023)
Learners or students interpret the factors that influence their success or failure in learning. It is called causal attribution. In the perspective of educational psychology, causal attribution is one of the cognitive factors that underlies the process of motivation in learning. Learners' perceptions of their successes and failures can affect their affection, cognition, and behavior in learning. This paper discusses causal attribution, both in terms of its dimensions, how it influences the learning process, what factors influence it, and how to develop positive attributions in students. The method used in this paper is a literature review. Conclusions and suggestions for future research are presented at the end